Comparative assessment of antibiotic resistance among first and second year undergraduate medical students in a tertiary care teaching hospital - Gupta, Rohini; Malhotra, Apoorva; Malhotra, Pavan (International Journal of Research in Medical Sciences, 2019)
Background: Antibiotics are one of the commonest prescribing drugs in day to day practice. However indiscriminate and irrational use of antibiotics has given rise to the emergence of antibiotic resistance. Thus, intervention in the form of educating students and making them aware about this important concept should be initiated at the gross root level right from the beginning of medical profession. Objective was to assess the comparative awareness regarding antimicrobial resistance between first and second year MBBS students. Methods: This was a comparative, cross-sectional questionnaire based study. Two forty six undergraduate medical students, 118 students from 1st year and 129 students from 2nd year MBBS were included in the study to assess the extent of knowledge and about the problem of antibiotic resistance. Self-administered questionnaire was used to collect the data from respondents. The questionnaires of both the groups were analyzed for the responses of the students and were compared using student ‘t’ test and chi-square test. Results: Majority of the participants 63.6% and 72.9% had completed the full course of antibiotics as prescribed by the physician. Statistically significant difference (p<0.05) was found between the two groups where in 58.4% of the first year and 16.3% of the second year students were of the view that antibiotics can be used for viral illnesses. Only 44.1% students of first year knew the reasons for antibiotic resistance. Conclusions: It can be concluded from the present study that second year medical students were more aware regarding antimicrobial resistance as compared to first year MBBS students who represented the general public. Thus, it is very important to educate the students in a practical manner about this concept as they are the future health care givers who can promote the rational use of antibiotics in near future.